2004
DOI: 10.1016/s0167-9317(04)00190-x
|View full text |Cite
|
Sign up to set email alerts
|

Processing issues in top?down approaches to quantum computer development in silicon

Abstract: We describe critical processing issues in our development of single atom devices for solid-state quantum information processing. Integration of single 31 P atoms with control gates and single electron transistor (SET) readout structures is addressed in a silicon-based approach. Results on electrical activation of low energy (15 keV) P implants in silicon show a strong dose effect on the electrical activation fractions. We identify dopant segregation to the SiO 2 /Si interface during rapid thermal annealing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We note that recent studies of P-implanted silicon by spreading resistance analysis (SRA) have shown the opposite trend-that the apparent activation ratio increases with increasing implant dose [7,22]. This discrepancy might possibly be explained by the presence of a native (poor quality) oxide with a high trap density in very close proximity to the implanted region, caused by cutting the wafer at a very shallow angle.…”
Section: Implant Activation At Room Temperaturementioning
confidence: 62%
See 1 more Smart Citation
“…We note that recent studies of P-implanted silicon by spreading resistance analysis (SRA) have shown the opposite trend-that the apparent activation ratio increases with increasing implant dose [7,22]. This discrepancy might possibly be explained by the presence of a native (poor quality) oxide with a high trap density in very close proximity to the implanted region, caused by cutting the wafer at a very shallow angle.…”
Section: Implant Activation At Room Temperaturementioning
confidence: 62%
“…If a significant density of electrons are caught in traps at the native oxide interface they do not contribute to conduction, so that the number of free electrons appears lower than that expected due to the implant dose. This effect would be particularly significant at low implant dose, where the native oxide trap density is much higher than the P density, but would be less important at high doses, leading to an apparent activation ratio that increases with increasing implant dose, as observed in [7,22]. If this is the case, it means that spreading resistance measurements are not well suited to measurements of low dose, near surface implants; however, more work on understanding the difference between these two measurement techniques is required (see, for example, [23]).…”
Section: Implant Activation At Room Temperaturementioning
confidence: 99%
“…Since Kane's original proposal in 1998 [1], the promise of implementing quantum computation (QC) with spin qubits in silicon has generated much excitement. Advantages such as long spin decoherence times [2][3][4] and mature silicon technologies have been exploited and expanded in recent QC scaling strategies [5]. In donor spin QC architectures impurities are arranged in large ordered arrays on the silicon chip and placed in a strong magnetic field so that spin states of the donors can be manipulated by resonant microwave pulses.…”
mentioning
confidence: 99%